Assessment of Socio-Economic Sustainability and Resilience after COVID-19 - D'Adamo, Idiano (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The pandemic period has caused severe socio-economic damage, but it is accompanied by environmental deterioration that can also affect economic opportunities and social equity. In the face of this double risk, future generations are ready to be resilient and make their contribution not only on the consumption side, but also through their inclusion in all companies by bringing green and circular principles with them. Policy makers can also favor this choice.